Transparência dos jurisdicionados do Tribunal de Contas do Estado do Pará: um estudo avaliativo - COSTA, Jessika Caroline Souza (Universidade Federal do Pará, 2022)
Technological advancement, the young Brazilian democracy, the process of public governance and accountability, as well as the constant waves of corruption, imposed a greater demand on the part of the population so that the public accounts were evidenced by the bodies responsible for executing and inspecting them, highlighting the theme of public transparency in Brazilian institutional, academic and social debates. In addition, several studies show that there is a high correlation between the levels of public transparency and the socioeconomic indices of a locality. Whereas the social indicators of the Amazon region reveal that the State of Pará has numerous vulnerabilities, whether of a social or even ecological nature; that the Court of Auditors of the State of Pará assumes the institutional mission of overseeing the transparency of the state bodies of that entity; and that the hypothesis of this research was based on the lack of high publicity of information by these bodies, the following research question arose: What is the current level of public transparency of the jurisdicted bodies of the Court of Auditors of the State of Pará, according to the current legislation? This time, with the objective of evaluating, based on the current access to information legislation, the level of transparency (active, passive and good practices) of the bodies that are under the jurisdiction of TCEPA. To this end, we sought to develop a research of a descriptive nature with a qualitative and quantitative approach and application of the evaluation methodology developed by the National Strategy to Combat Corruption and Money Laundering (ENCCLA) in a multiple case study. As research techniques, bibliographic and documentary research were used. The latter was based on sources of documentary evidence from the jurisdictions of TCEPA available on the internet and accessible to citizens' request for access. The results pointed to a scenario of critical and deficient transparency on the websites of the jurisdictional units of TCEPA, in which, the agencies did not reach 50% of the proposed Transparency Index. In view of this, improvements were proposed in the process of disclosing the public information of the agencies, pointing out good management practices for units with insufficient levels of transparency, as well as instrumentalizing the supervisory and pedagogical performance of Pará's external control regarding access to information from the TCEPA's jurisdictional authorities.